ANALISIS PENGADAAN TANAH BAGI KEPENTINGAN UMUM DI KABUPATEN LUWU TIMUR - Haedar Djidar; Kasmad Kamal; Indra Wijaya (Halu Oleo University, 2024)
This research aims to find out and analyze how the implementation of land acquisition for development for public interest in East Luwu Regency. To find out what are the obstacles in the implementation of land acquisition for development in the public interest in East Luwu Regency. This research was conducted using the Normative Empirical legal research method, research was conducted in East Luwu Regency. The implementation of land acquisition in East Luwu Regency is carried out in accordance with applicable laws and regulations. Where the implementation process is carried out by planning, preparation, implementation and then delivery of results. Obstacles in implementing land acquisition in East Luwu Regency are related to the lack of budget funds in procuring capital expenditures, as well as the amount of compensation determined by the government based on an assessment, which is binding.